Reproduction of Institutions through People’s Practices: Evidences from a Gram Panchayat in Kerala - Rajesh K (The Institute for Social and Economic Change, 2010)
This paper analyses the dynamics of participatory institutions in Kodayathur Gram Panchayat in Kerala. It also explores how the different fields of society in panchayat internalised and reproduced these institutions through their actual practices. The study has adopted a relational methodology, linking the subjective stand point of individuals or groups, affiliated to institutions, with their objective position in the society. It has applied methods like in-depth dialogues with informants along with group discussions and document analysis. The study reached the conclusion that institutions in GP largely failed in achieving their objectives. Apathetic approach of the political parties, aversion of the middle and upper middle class groups towards public institutions, and inability of the marginalised groups in involving such institutions were the major hurdles in achieving their ideal objectives.